1999
DOI: 10.1021/jp9913867
|View full text |Cite
|
Sign up to set email alerts
|

Nanocrystalline Mesoporous Strontium Titanate as Photoelectrode Material for Photosensitized Solar Devices:  Increasing Photovoltage through Flatband Potential Engineering

Abstract: Nanocrystalline SrTiO 3 is synthesized by hydrothermal treatment of nanocrystalline titanium dioxide in the presence of strontium hydroxide. Working photoelectrochemical solar cells are produced using these nanometersized semiconductor particles as photoelectrode materials. At AM 1.5, measured open circuit voltages were roughly 100 mV higher than in solar cells produced using nanocrystalline titanium dioxide (anatase), in agreement with a simple relation between semiconductor conduction band edge and open circ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
178
0
5

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 270 publications
(189 citation statements)
references
References 22 publications
6
178
0
5
Order By: Relevance
“…Among them, nanocrystalline TiO2 and ZnO have been found to be the best materials owing to their high performance in DSSCs. In addition to these binary oxides, ternary oxides such as Zn2SnO4 [26], BaSnO3 [27], and SrTiO3 [28] have been investigated because of the ease of modifying their chemical properties and band structures. Different surface modifications of different photoanodes are described in detail in the following sections.…”
Section: Surface Modifications Of Photoanodementioning
confidence: 99%
“…Among them, nanocrystalline TiO2 and ZnO have been found to be the best materials owing to their high performance in DSSCs. In addition to these binary oxides, ternary oxides such as Zn2SnO4 [26], BaSnO3 [27], and SrTiO3 [28] have been investigated because of the ease of modifying their chemical properties and band structures. Different surface modifications of different photoanodes are described in detail in the following sections.…”
Section: Surface Modifications Of Photoanodementioning
confidence: 99%
“…Strontium titanate, SrTiO 3 (ST), is arguably the prototypical member of this structure family, not only because it can be made to exhibit a diverse range of unusual properties itself. Moreover, STO is an important n-type semiconductor with band gap of about 3.2 eV [2], and it has been widely studied not only because of its variety of outstanding physical properties (stability, wavelength response, and current-voltage) but also for its practical applications, such as their high static dielectric constant and good insulation [3,4], their use in grain boundary barrier-layer capacitors [5], resistive oxygen gas sensors [6,7], solar cells [8], solid oxide electronic device [9], at large scale, as substrate at the time of growth of thin films perovskite compounds [10], and promising candidate for efficient photocatalysts [11] and photoelectrodes [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…We chose hydroxypropyl cellulose (HPC) for this study because HPC is often used as a thickener in preparing the porous metal oxide electrodes of DSSCs. 13,14) We prepared Pt electrodes by the thermal decomposition of H 2 PtCl 6 with and without HPC in the precursor solution. We found that HPC prevents the agglomeration of Pt particles during the thermal decomposition of H 2 PtCl 6 and leads to an increased surface area of Pt on the Pt electrode.…”
Section: Introductionmentioning
confidence: 99%